2004
DOI: 10.1016/j.drugalcdep.2003.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Personality profile and drug of choice; a multivariate analysis using Cloninger’s TCI on heroin addicts, alcoholics, and a random population group

Abstract: As personality may predispose, precipitate or perpetuate substance abuse and/or dependence, and as it is considered to remain stable across the years in a given subject, potential links with the drug of choice may help screen future patients before drug consumption. The present study compared three groups: 42 patients with heroin dependence (mean age: 31.2; standard deviation (SD): 5.5; 10 females), 37 patients with alcohol dependence (mean age 44.2; SD: 9.1; 9 females) and 83 subjects from a random population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(65 citation statements)
references
References 55 publications
(59 reference statements)
8
56
0
1
Order By: Relevance
“…A recent study using TCI reported that heroin users scored higher than subject with an alcohol-related disorder on novelty-seeking and self-directedness, and that exploratory excitability (a sub-dimension of novelty-seeking) was the best variable to segregate these groups. Subject with an alcohol dependence also had a lower score than controls for certain subscales of reward dependence [32]. Our study confirms some of these results.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A recent study using TCI reported that heroin users scored higher than subject with an alcohol-related disorder on novelty-seeking and self-directedness, and that exploratory excitability (a sub-dimension of novelty-seeking) was the best variable to segregate these groups. Subject with an alcohol dependence also had a lower score than controls for certain subscales of reward dependence [32]. Our study confirms some of these results.…”
Section: Discussionsupporting
confidence: 86%
“…Some personality features have been commonly linked to patients with SUD, the most salient variables being novelty-seeking [30,31], impulsivity, and low harm avoidance [32,33]. Few studies have tried to differentiate between drug preferences (voir réf 36) and none have studied this among jailed substance users.…”
Section: Discussionmentioning
confidence: 99%
“…Novelty seeking, which is considered to be associated with low basal dopaminergic activity, has been reported to be associated with both nicotine consumption and heavy caffeine intake, both of which enhance dopaminergic neurotransmission [5]. Because personality may predispose, precipitate, or perpetuate substance addiction and/or dependence [7], information on personality traits might be useful in the management of addictive disorders and may assist clinicians in matching interventions to relevant personality traits [8].…”
Section: Introductionmentioning
confidence: 99%
“…Drug addiction was selected for comparison with internet addiction since the personality traits of substance abusers are well known [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased HA has been observed in those dependent on tobacco, 11 alcohol, 12 and heroin. 12 However, other studies did not obtain consistent results for HA. 13,14 There are few studies reporting associations with RD-lower levels were associated with drug dependence 15 and adolescent substance use 16 but not heroin/alcohol dependence 12 -and even fewer results for PE, where in one study lower levels were associated with daily smoking, 11 but in another study PE did not differentiate heroin-or alcohol-dependent patients from controls.…”
Section: Introductionmentioning
confidence: 99%